2019
DOI: 10.3389/fmicb.2019.02607
|View full text |Cite
|
Sign up to set email alerts
|

Combined Action of Piperitenone Epoxide and Antibiotics Against Clinical Isolates of Staphylococcus aureus and Escherichia coli

Abstract: The aim of this study was to determine the antimicrobial efficiency of piperitenone epoxide (PEO) – a principal component of various aromatic plants’ essential oil – in combination with various antibiotics against 28 strains of Staphylococcus aureus and 10 strains of Escherichia coli isolated from clinical samples. Mentha spicata’s essential oil, initially collected by hydrodistillation, was then subjected to flush column chromatography affording PEO of high purity. Minimum inhibitory concentrations of PEO alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Their combined use has shown the capability to reduce the antibiotic concentrations of employees and, consequently, to decrease the toxic effects during the therapy. These results highlight the ability of essential oils to be a potential modulating agent of antibiotic resistance, as has already emerged from other studies [ 45 , 46 , 47 , 48 , 49 ]. The use of natural antimicrobial agents is increasingly expanding, also thanks to new biotechnologies, such as the incorporation of essential oils in polymeric nanoparticles [ 50 ], a technology used to obtain an increase in antibacterial and antioxidant activity, with a reduction of toxic effects and a better penetration into the biofilm [ 51 ].…”
Section: Discussionsupporting
confidence: 79%
“…Their combined use has shown the capability to reduce the antibiotic concentrations of employees and, consequently, to decrease the toxic effects during the therapy. These results highlight the ability of essential oils to be a potential modulating agent of antibiotic resistance, as has already emerged from other studies [ 45 , 46 , 47 , 48 , 49 ]. The use of natural antimicrobial agents is increasingly expanding, also thanks to new biotechnologies, such as the incorporation of essential oils in polymeric nanoparticles [ 50 ], a technology used to obtain an increase in antibacterial and antioxidant activity, with a reduction of toxic effects and a better penetration into the biofilm [ 51 ].…”
Section: Discussionsupporting
confidence: 79%
“…Different investigations had discussed the efficacy of essential oils against gram positive and negative bacteria, and showed that gram positive bacteria more susceptible to oils [13][14]. However, in [15], reported different results where EO in combination with antimicrobial drugs considerably reduced the effective doses of the drugs used with E. coli isolates despite relatively high MIC values of this EO. In our study, missing data like the minimum bactericidal concentration were not estimated; more numbers of isolates should be tested to assess the efficacy of EEO and different antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Their antibacterial activity has been recently studied against pathogenic bacteria frequently responsible for hospital-acquired infections (HAIs) [ 21 , 22 , 23 , 24 , 25 ]. Recent studies have also highlighted the synergistic action of EOs with other antimicrobial drugs and how these associations could be used to positively modulate the antimicrobial activity of some antibiotics against antibiotic-resistant bacteria, with a consequent decrease in the minimum effective dose of the drugs [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%